Identification of patients with defects in the globin genes by studying the blood parameters and genetic study: a Case Report - Domenico Dell'Edera; Giusi Natalia Milazzo; Antonio Malvasi; Andrea Tinelli; Manuela Leo; Carmela Santacesaria; Arianna Allegretti; Elena Pacella; Rocchina Barbieri; Maria Brigida Lioi; Annunziata Anna Epifania (Mediterranean Journal of Hematology and Infectious Diseases, 2014)
Hemoglobinopathies constitute a major health problem worldwide, with a high carrier frequency, particularly in certain regions where malaria has been endemic. These disorders are characterized by a vast clinical and hematological phenotypic heterogeneity. The increase of the HbA2 is an invaluable hematological marker of the beta-thalassemia heterozygosis and the double heterozygosis for alleles of delta- and alpha-globin genes or for alleles of delta- and beta-globin genes can cause the decrease of the HbA2 up to normal or borderline values.The aim of this paper is to highlight as sometimes the only biochemical diagnosis is not exhaustive and a molecular diagnostic widening is necessary to detect the genetic deficiency that is the reason of the thalassemic trait.